Acoustic emission monitoring of damage progression in 3D braiding composite shafts during torsional tests. (15th January 2019) - Hao, Wenfeng; Yuan, Zengrui; Tang, Can; Zhang, Lu; Zhao, Guoqi; Luo, Ying
Abstract: In this work, damage progression in 3D braiding composite shafts during torsional tests was monitored using the acoustic emission (AE) method. The 3D 4-directional braided composite shafts with various braiding angles were prepared using Vacuum Assisted Resin Transfer Moulding (VARTM). The torsional tests were performed on the static torsion machine and the AE method was used to monitor the damage progression. The continuous wavelet transform method was used to analyze the AE signals for time-frequency analysis. The accumulated damage is manifested via matrix cracking, fiber bundle-matrix debonding, and fiber breakage, which were identified by the frequency of the AE signals. The failure modes and the mechanisms of the 3D 4-directional braided composite shafts were characterized. The results will enable the design and the application of the 3D 4-directional braided composite shafts within engineering.